EFFECT OF MELATONIN ON PANCREATIC AUTOPHAGY IN RATS WITH GESTATIONAL DIABETES MELLITUS AND THE MECHANISM - ZHENG Qingqing, LI Chao, LI Yan, QIAO Binglong, MA Chunling (精准医学杂志, 2023)
Objective To investigate the effect of melatonin on pancreatic autophagy in rats with gestational diabetes mellitus (GDM) and the underlying mechanism. Methods Twenty-eight rats were randomly divided into A group (rats with normal pregnancy), B group (rats with GDM), C group (low-dose melatonin administration for rats with GDM), and D group (high-dose melatonin administration for rats with GDM), with seven rats in each group. All the groups were examined for the se-rum levels of glucose, insulin, and glycosylated hemoglobin. Pancreatic tissue slices were prepared to examine the pathological changes of the pancreas with hematoxylin-eosin (HE) staining, the apoptosis of pancreatic cells with TUNEL staining, and the autophagy of the pancreatic tissue with transmission electron microscopy. Western blot was used to measure the expression of autop-hagy-related proteins in the pancreatic tissue: microtubule-associated protein 1 light chain 3 (LC3), Beclin1, phosphorylated phosphatidylinositol 3-kinase (p-PI3K), PI3K, phosphorylated protein kinase B (p-AKT), AKT, phosphorylated mammalian target of rapamycin (p-mTOR), and mTOR. Results There were significant differences in serum glucose, insulin, and glycosylated hemoglobin levels between different groups (F=52.26-66.73,P<0.05). Compared with those of group A, the levels of serum glucose, insulin, and glycosylated hemoglobin in group B were significantly increased (t=-14.45-7.23,P<0.05). Compared with group B, groups C and D showed significantly decreased serum glucose, insulin, and glycosylated hemoglobin levels (t=-5.32-10.02,P<0.05). The results of HE staining, TUNEL staining, and transmission electron microscopy revealed that compared with group A, group B showed increased levels of pathological damage, apoptosis, and autophagy in the pancreatic tissue; groups C and D showed reduced pathological damage, apoptosis, and autophagy in the pancreatic tissue than group B. Western blot detected significant differences in the levels of LC3 Ⅱ/LC3 Ⅰ, p-PI3K/PI3K, p-AKT/AKT, and p-mTOR/mTOR and the relative expression of Beclin1 in the pancreatic tissue between different groups (F=27.68-67.72,P<0.05). Compared with group A, group B showed significantly increased levels of LC3 Ⅱ/LC3 Ⅰ and Beclin1 (t=-8.13--6.83,P<0.05) and significantly decreased levels of p-PI3K/PI3K, p-AKT/AKT, and p-mTOR/mTOR in the pancreatic tissue (t=8.83-14.05,P<0.05). Compared with group B, groups C and D showed significantly reduced levels of LC3 Ⅱ/LC3 Ⅰ and Beclin1 (t=3.36-6.95,P<0.05) and significantly increased levels of p-PI3K/PI3K, p-AKT/AKT, and p-mTOR/mTOR in the pancreatic tissue (t=-9.64--3.51,P<0.05). Conclusion Melatonin can relieve pancreatic damage in rats with GDM, which may be through regulating the PI3K/AKT pathway to inhibit the autophagy of the pancreatic tissue.